2021
DOI: 10.1021/acs.biomac.1c00775
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Site-Specific Interferon-α2a Bioconjugates Originated from PEG, LPG, and PEtOx

Abstract: Conjugation of biologics with polymers modulates their pharmacokinetics, with polyethylene glycol (PEG) as the gold standard. We compared alternative polymers and two types of cyclooctyne linkers (BCN/DBCO) for bioconjugation of interferon-α2a (IFN-α2a) using 10 kDa polymers including linear mPEG, poly­(2-ethyl-2-oxazoline) (PEtOx), and linear polyglycerol (LPG). IFN-α2a was azide functionalized via amber codon expansion and bioorthogonally conjugated to all cyclooctyne linked polymers. Polymer conjugation did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(79 citation statements)
references
References 99 publications
4
74
1
Order By: Relevance
“…This can be carried out either by applying different initiators or postmodification of the end group subsequent to the polymerization process [5,33,36,[83][84][85]. LPG has been successfully conjugated to proteins via different chemistries, including random conjugation to bovine serum albumin (BSA) [33], site-specific CuAAC to Exenatide, N-terminally to Interleukin-4 [86], and Anakinra [87] and to IFN-α-2a via SPAAC [88]. These studies clearly demonstrated a comparable size of PEGylated and LPGylated proteins with a similar half-life extension in vivo.…”
Section: Drug Delivery Systems Protein and Surface Conjugationmentioning
confidence: 99%
“…This can be carried out either by applying different initiators or postmodification of the end group subsequent to the polymerization process [5,33,36,[83][84][85]. LPG has been successfully conjugated to proteins via different chemistries, including random conjugation to bovine serum albumin (BSA) [33], site-specific CuAAC to Exenatide, N-terminally to Interleukin-4 [86], and Anakinra [87] and to IFN-α-2a via SPAAC [88]. These studies clearly demonstrated a comparable size of PEGylated and LPGylated proteins with a similar half-life extension in vivo.…”
Section: Drug Delivery Systems Protein and Surface Conjugationmentioning
confidence: 99%
“…Polymer synthesis of LPG and PEG was performed as described previously [49]. In brief, LPG was synthesized by monomer-activated anionic ring-opening polymerization.…”
Section: Synthesis Of Polymersmentioning
confidence: 99%
“…Therefore, we recently synthesized bioconjugates through strain-promoted azide-alkyne cycloaddition (SPAAC), starting off a genetically engineered, azido-IFN-α2a mutant and functionalized PEG, and LPG polymers of about 10 kDa, respectively [49]. All products were generally comparable across the two polymer chemistries reported here, including their preferential interaction sites with the protein-surface.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations